2015
DOI: 10.1080/21622965.2014.960567
|View full text |Cite
|
Sign up to set email alerts
|

Executive Function and Emotion Regulation Strategy Use in Adolescents

Abstract: Development of emotion regulation strategy use involves a transition from reliance on suppression during childhood to greater use of reappraisal in adolescence and adulthood-a transition that parallels developmental changes in executive functions. We evaluated the relationship between emotion regulation strategy use and executive functioning in the everyday life of 70 typically developing adolescents who completed the Emotion Regulation Questionnaire for Youth and the Behavior Rating Inventory of Executive Fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 26 publications
5
76
3
2
Order By: Relevance
“…As discussed above, explicit strategies of cognitive reappraisal (reinterpreting emotion-eliciting scenarios in a more positive light) and expressive suppression (reducing the outward display of an emotional reaction) have received the most empirical attention, both in adolescence and in emotion regulation research in general. In a recent study by Lantrip et al (2015) although it was found that reappraisal use was associated with better executive functions in a group of adolescents (aged 12-18), there were no age related differences in strategy use. However, the sample size of this study was relatively small (N=70) in comparison to a longitudinal study of 1,128 adolescents (Gullone et al, 2010).…”
Section: B Explicit Emotion Regulationmentioning
confidence: 71%
“…As discussed above, explicit strategies of cognitive reappraisal (reinterpreting emotion-eliciting scenarios in a more positive light) and expressive suppression (reducing the outward display of an emotional reaction) have received the most empirical attention, both in adolescence and in emotion regulation research in general. In a recent study by Lantrip et al (2015) although it was found that reappraisal use was associated with better executive functions in a group of adolescents (aged 12-18), there were no age related differences in strategy use. However, the sample size of this study was relatively small (N=70) in comparison to a longitudinal study of 1,128 adolescents (Gullone et al, 2010).…”
Section: B Explicit Emotion Regulationmentioning
confidence: 71%
“…This decreased use of expressive suppression seems to indicate that adolescents learn that expressive suppression is not an adaptive emotion regulation strategy with age; however, it is hard to interpret the decreased use of cognitive reappraisal since the adolescents were expected to learn to use healthier emotion regulation approaches (John and Gross, 2004). In another study, Lantrip et al (2016) found no age effects for cognitive reappraisal or expressive suppression. However, it should be noted that their sample size was small ( N = 70).…”
Section: Introductionmentioning
confidence: 89%
“…Based on these findings, a few studies have investigated the development of the tendency to use cognitive reappraisal/expressive suppression in adolescence (e.g., Gullone et al, 2010; Lantrip et al, 2016; Gómez-Ortiz et al, 2016). Gullone et al (2010) and Gómez-Ortiz et al (2016) found that adolescents reported using less cognitive reappraisal and expressive suppression with increasing age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficit in inhibition of negative stimuli processing is related with difficulty in reappraising [3] [4], decreased cognitive flexibility is associated with rumination [5], and normal executive function is related with a frequent use of reappraisal (compared to expressive suppression) [6]. The function of cognitive control network (CCN), which includes the dorsal anterior cingulate cortex (dACC), DLPFC and posterior parietal regions [7], may be critical to reappraisal, through the allocation of resources to goal directed behaviors it facilitates.…”
Section: Executive Function and Its Neural Correlates And Dysregulatimentioning
confidence: 99%